Impact of mobile intensive care unit use on total ischemic time and clinical outcomes in ST-elevation myocardial infarction patients – real-world data from the Acute Coronary Syndrome Israeli Survey. Issue 6 (September 2018) - Koifman, Edward; Beigel, Roy; Iakobishvili, Zaza; Shlomo, Nir; Biton, Yitschak; Sabbag, Avi; Asher, Elad; Atar, Shaul; Gottlieb, Shmuel; Alcalai, Ronny; Zahger, Doron; Segev, Amit; et al.
Background: Ischemic time has prognostic importance in ST-elevation myocardial infarction patients. Mobile intensive care unit use can reduce components of total ischemic time by appropriate triage of ST-elevation myocardial infarction patients. Methods: Data from the Acute Coronary Survey in Israel registry 2000–2010 were analyzed to evaluate factors associated with mobile intensive care unit use and its impact on total ischemic time and patient outcomes. Results: The study comprised 5474 ST-elevation myocardial infarction patients enrolled in the Acute Coronary Survey in Israel registry, of whom 46% ( n =2538) arrived via mobile intensive care units. There was a significant increase in rates of mobile intensive care unit utilization from 36% in 2000 to over 50% in 2010 ( p <0.001). Independent predictors of mobile intensive care unit use were Killip>1 (odds ratio=1.32, p <0.001), the presence of cardiac arrest (odds ratio=1.44, p =0.02), and a systolic blood pressure <100 mm Hg (odds ratio=2.01, p <0.001) at presentation. Patients arriving via mobile intensive care units benefitted from increased rates of primary reperfusion therapy (odds ratio=1.58, p <0.001). Among ST-elevation myocardial infarction patients undergoing primary reperfusion, those arriving by mobile intensive care unit benefitted from shorter median total ischemic time compared with non-mobile intensive care unit patients (175 (interquartile range 120–262) vs 195 (interquartile range 130–333) min, respectively ( p <0.001)). Upon a multivariate analysis, mobile intensive care unit use was the most important predictor in achieving door-to-balloon time <90 min (odds ratio=2.56, p <0.001) and door-to-needle time <30 min (odds ratio=2.96, p <0.001). One-year mortality rates were 10.7% in both groups (log-rank p -value=0.98), however inverse propensity weight model, adjusted for significant differences between both groups, revealed a significant reduction in one-year mortality in favor of the mobile intensive care unit group (odds ratio=0.79, 95% confidence interval (0.66–0.94), p =0.01). Conclusions: Among patients with ST-elevation myocardial infarction, the utilization of mobile intensive care units is associated with increased rates of primary reperfusion, a reduction in the time interval to reperfusion, and a reduction in one-year adjusted mortality.